A 30 Years Old Woman with Sepsis, Skin and Soft TissueInfection, and Obesity - Widinartasari, Franzeska ADM; Sodiq, Muhammad Ali; Sofro, Muchlis AU (UI Scholars Hub, 2017)
Obesity increases morbidity and mortality through its multiple efects on nearly every human system. Obesity has efect on the immune response which leads to susceptibility to infections. ß lactamases are bacterial enzymes that inactivate ß-lactam antibiotics by hydrolysis. One group of ß lactamases, extended-spectrum ß lactamases (ESBLs), have the ability to hydrolyse and cause resistance to various types of the newer ß-lactam antibiotics. The management of skin and soft tissue infection with polymicrobial infection and multi drug resistance can be challenging problem. We present a case of an obese patient with polymicrobial SSTI. bPatient showed clinical sign of sepsis with acute kidney injury. With fluid rescucitation, early antibiotic administration and surgical treatment, she gained clinical improvement. The key to successful management of patients with severe skin and soft tissue infection are early recognition and complete surgical debridement. Clinicians need to consider appropriate early empirical antibiotic combination therapy coverage or the use of combination therapy to treat SSTI